Peer review in the development of academic articles: Experiences of Finnish authors in the educational sciences. Issue 2 (27th September 2018) - Atjonen, Päivi
Abstract : This research examined author experiences of the developmental feedback regarding peer review of journal articles. It focused on quite experienced authors in the educational sector of all eight universities in Finland. Data were gathered using an electronic questionnaire, which was completed by 121 respondents. The majority of authors perceived reviewer feedback as developmental and appreciated critical but constructive review. Over 60% of respondents found reviewers usually keen to improve the article and to provide pertinent critique. Less than 8% reported frequent experience of reviewers who were not experts or provided unjustified accusations. A third reported reviewer feedback that was frequently biased or based on different paradigms. The most published authors were the most satisfied with the developmental feedback, but postdoctoral researchers had received more developmental complementary feedback than any other groups. The results indicate that the peer review system remains useful for ensuring article quality, but some attention is still required to ensure developmental feedback that will help the authors enhance their manuscripts.